Cyclical Variations and Trend in Occupational Wage Differentials in American Industry Since 1914 - Bell, Philip W. (The Review of Economics and Statistics, 1951)
1ASED on admittedly scarce stuidies, the prevalent feeling concerning movements in occupational wage differentials in the United States seems to be that there has been a trend toward a narrowing of the percentage differential between skilled and unskilled workers during the past half-century, and that this trend is accentua,ted in boom periods of full em.ploynment and reversed in depressions.2 Thils article has a threefold purpose: to indicate some of the failings of the studies made thus far on this topic, to sketch briefly the results of an empirical study of changes in occupational differentials, pointing out an important exception to the conventional mode]. (the depressionof I929-33), and to analyze changes in the occupational wage structure which have occurred.